Semiotic Analysis of Roland Barthes on the Movie Poster "Like and Share" - Rifda Apriliani Nazwa; Indah Wenerda (Jurnal Indonesia Sosial Teknologi, 2024)
The film Like and Share discusses sexual violence against women who are still in school and experience a lot of pressure. The purpose of this study is to examine the visual semiotics of the Like and Share poster through Roland Barthes' theory by dissecting the meaning of signs into denotations, connotations, and myths on the Like and Share movie poster. Not only looking at the poster from the visual side, but also understanding more deeply about the important issues facing teenagers today. This study uses a qualitative descriptive method in analyzing and interpreting meaning. In this analysis, marks can be found on the visual elements of the poster such as typography, colors, layout, and images to identify hidden meanings to the audience.